Enhancing medication literacy: a vital step in combating hypertension in Pakistan - Khan, Shahzaib; Muhammad Tayyab Malik; Gandapur, Mah Munir; Naz, Khadeeja (Journal of the Pakistan Medical Association, 2025)
Madam, Medication literacy refers to the ability of individuals to acquire, understand, convey, calculate, and process patient-specific information about their medications. This competency them to make informed decisions regarding their medication and health, ensuring safe and effective use of their treatments.(1) Medication literacy is considered crucial in addressing the ailments encountered by the general population. Hypertension is a prevalent medical condition, particularly in developing countries, where it poses a significant public health challenge. An estimated 75% of individuals with hypertension—approximately 639 million people—reside in these regions, where healthcare facilities are often limited. Low awareness of the risks associated with hypertension, coupled with inadequate access to proper medical care, contributes to poor blood pressure management and increased health complications.(2) Pakistan, as a developing country, is also grappling with the challenges posed by hypertension. According to the National Health Survey of Pakistan, hypertension impacts 18% of adults and 33% of individuals over the age of 45, with only 50% of the accurately diagnosed, and of these, only 50% receive appropriate treatment..(3) This is particularly concerning because hypertension has severe health implications on its own. When combined with comorbidities such as obesity, type 2 diabetes, dyslipidemia, and metabolic syndrome, the associated risks are significantly heightened. It is also frequently linked with conditions like kidney disease, sleep apnea, and even depression.(4) Hypertension presents a considerablechallenge for public health services in economically developing countries. However, medication literacy plays a crucial role in managing blood pressure levels among hypertensive individuals. A study conducted in China found that medication literacy had a substantial impact on blood pressure control rates among hypertensive patients.(5) Addressing the widespread issue of hypertension in Pakistan necessitates a multifaceted, government-led approach.. A multifaceted, government-led approach is essential to tackle this challenge effectively. This should include nationwide health awareness seminars, encouraging doctors to actively promote medical literacy among patients, and emphasising the importance of medication adherence, particularly in rural areas where healthcare access is limited. Additionally, research councils should promote further studies on this issue while expanding their focus to other prevalent diseases in Pakistan. Such measures would contribute to a healthier, more informed population and significantly reduce disease prevalence.